Erythropoietin and ferritin response in native highlanders aged 4–19 years from the Leh‐Ladakh region of India. (26th November 2018) - Yanamandra, Uday; Senee, Harikishan; Yanamadra, Sushma; Das, Subrat K.; Bhattachar, Srinivas A.; Das, Reena; Kumar, Suman; Malhotra, Pankaj; Varma, Subhash; Varma, Neelam; Nair, Velu
Summary: The pivotal role of erythropoietin (EPO) in hypoxic adaptation has led to various studies assessing the EPO and ferritin response in native highlanders from Andes and Tibet. We assessed the relationship between EPO, haemoglobin and ferritin in 335 native highlanders (172 boys and 163 girls, aged 4 to 19 years) from Leh‐Ladakh, India, who had no history of travel to lowland areas. Complete blood counts, serum EPO and ferritin levels were measured. We stratified study subjects based on age, gender, pubertal status and analysed the EPO and ferritin levels between the stratified groups respectively. The mean EPO level in boys was lower than girls. The mean ferritin level in boys was significantly higher ( P = 0·013) than in girls. There was no significant variation in the EPO and ferritin levels amongst the various age groups in our study. Near normal EPO levels since childhood with a negative correlation with haemoglobin is suggestive of a robust adaptive mechanism to high altitude from the early years of life. Low ferritin levels are indicative of decreased iron stores in these native highlanders.